Aging-resistant and highly flame-retardant polyurethane integral skin foam material and preparation method and application thereof

By designing polyurethane self-skinned foam materials of components A and B, and combining silane coupling agents and biomass raw materials, the problems of insufficient aging resistance and flame retardant performance of polyurethane self-skinned foam materials are solved, and the high performance performance of the material in various environments is achieved.

CN119286235BActive Publication Date: 2025-04-04SHANDONG INOV POLYURETHANE

Patent Information

Application Number
CN202411807127.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing polyurethane self-crusting foam materials have poor aging resistance during long-term use and insufficient flame retardant performance, making it difficult to meet the requirements of high temperature, humidity, low temperature and various environmental changes.

Method used

Aging-resistant high flame retardant polyurethane self-crusting foam material is made of components A and components B at a mass ratio of 100: (45-55). Component A includes polyether polyols, polymer polyols, silane coupling agents, chain extenders, flame retardants, foaming agents, etc. Component B includes polyether polyols, composite antioxidants, pure MDI and liquefied MDI. By rationally designing catalysts and using biomass raw materials to synthesize high-efficiency flame retardants, the aging resistance and flame retardant properties of the material are improved.

Benefits of technology

The high temperature, humidity, low temperature, hydrophobic properties and flame retardant effects of polyurethane self-crusting foam material are achieved, so that the material still maintains good performance in different environmental changes and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyurethane self-skinning foam, and specifically relates to an aging-resistant high flame-retardant polyurethane self-skinning foam material and its preparation method and application. The aging-resistant high flame-retardant polyurethane self-skinning foam material is made of component A and component B in a mass ratio of 100: (45-55), component A includes: polyether polyol 1, polymer polyol, silane coupling agent, chain extender, flame retardant A, flame retardant B, foaming agent, foam stabilizer, composite catalyst, component B includes: polyether polyol 2, composite antioxidant, pure MDI, liquefied MDI. The aging-resistant high flame-retardant polyurethane self-skinning foam material of the present invention has excellent high temperature resistance, damp heat, low temperature, hydrophobic performance and flame retardant effect, so that the polyurethane self-skinning foam material can cope with different environmental changes; the present invention also provides its preparation method and application, the preparation process is simple, and the prepared product can be applied to a variety of occasions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane integral skin foams, and in particular relates to an aging-resistant and highly flame-retardant polyurethane integral skin foam material and a preparation method and application thereof. Background Art

[0002] Polyurethane integral foam is a material with a special structure, which is characterized by a dense skin layer and a foam core. During the foaming process, due to the contact between the material and the mold surface, the material on the surface layer reacts quickly to form a relatively dense structure, while the interior presents a foam-like structure. This unique structure gives polyurethane integral foam good strength and elasticity, and it also has light weight and excellent energy absorption performance. For this reason, polyurethane integral foam materials have been widely used in the fields of car seats, armrests, etc. In addition, it is also widely used in car steering wheels, PU armrests, headrests, bicycle saddles, motorcycle saddles, engine hoods and other products due to its light weight, heat insulation, shock absorption, noise reduction and other characteristics.

[0003] However, during long-term use, polyurethane self-skinning foam materials will be affected by environmental factors such as light, seasonal changes, and temperature changes, resulting in poor aging resistance. Specifically, the physical properties of the foam, such as strength and elasticity, gradually decrease, and the surface may become discolored or powdery.

[0004] In addition, in many application scenarios, such as transportation and building interiors, there are higher requirements for the flame retardant properties of materials. Good flame retardant properties can effectively slow down the spread of fire when a fire occurs, buy more time for personnel evacuation and fire extinguishing, and thus significantly reduce the losses caused by fire.

[0005] CN114716638A discloses a polyurethane integral skin foam and its preparation method and application. The polyether polysiloxane copolymer, amino polyether polyol, polyurea polymer polyol, water and carbodiimide modified isocyanate are used as raw materials. Through the coordinated coordination of several substances, the polyurethane integral skin foam has good flame retardancy, water resistance and other properties while ensuring the physical and mechanical properties of the integral skin foam. However, the polyurethane integral skin foam is greatly affected by the environment, and its water resistance and wear resistance are very likely to decrease to varying degrees after long-term use.

[0006] Therefore, it is necessary to conduct further research on polyurethane integral skin foam materials to meet the current high requirements for high temperature resistance, wet heat, low temperature resistance and flame retardant properties. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an aging-resistant and highly flame-retardant polyurethane self-skinning foam material. The prepared product has excellent high temperature resistance, humidity and heat resistance, low temperature, hydrophobicity and flame retardant effect, so that the polyurethane self-skinning foam material can cope with different environmental changes; the present invention also provides a preparation method and application thereof. The preparation process is simple and the prepared product can be applied to a variety of occasions.

[0008] The aging-resistant and highly flame-retardant polyurethane integral skin foam material of the present invention is made of component A and component B in a mass ratio of 100:(45-55), wherein component A includes the following raw materials in parts by mass:

[0009] Polyether polyol 1: 50-70 parts;

[0010] Polymer polyol: 30-50 parts;

[0011] Silane coupling agent: 1-3 parts;

[0012] Chain extender: 5-8 parts;

[0013] Flame retardant A: 10-15 parts;

[0014] Flame retardant B: 10-15 parts;

[0015] Foaming agent: 0.8-1.0 parts;

[0016] Foam stabilizer: 0.5-1.0 parts;

[0017] Composite catalyst: 0.6-1.2 parts;

[0018] Component B includes the following raw materials in parts by weight:

[0019] Polyether polyol 2: 5-8 parts;

[0020] Compound antioxidant: 0.9-1.5 parts;

[0021] Pure MDI: 20-40 parts;

[0022] Liquefied MDI: 50-75 parts.

[0023] The polyether polyol 1 has a number average molecular weight of 7000-8000, a functionality of 4-5, and a hydroxyl value of 28.5-32.5 mgKOH / g, and is preferably 10LD8005 produced by Shandong Bluestar Dongda Chemical Co., Ltd.

[0024] The polyether polyol 2 has a number average molecular weight of 400-600, a functionality of 3, and a hydroxyl value of 330-350 mgKOH / g.

[0025] The functionality of the polymer polyol is 3, the hydroxyl value is 19.0-23.0 mgKOH / g, and the solid content is 41.0-45.0%. CHP-H45D produced by Changhua Chemical Technology Co., Ltd. is preferred.

[0026] The flame retardant A is expandable graphite with a particle size of 80-100 meshes and an expandability of more than 300 times.

[0027] The flame retardant B is a nitrogen-phosphorus synergistic modified lignin flame retardant, which is prepared by firstly subjecting lignin and phosphoric acid solution to an esterification reaction, and then to a grafting reaction with melamine. The specific preparation process of the flame retardant B is as follows:

[0028] (1) reacting a 45 wt.% NaOH aqueous solution with corn straw powder at 45-50° C. for 1-1.5 h, then filtering, drying, washing and neutralizing, and freeze-drying to obtain lignin, wherein the mass ratio of the 45 wt.% NaOH aqueous solution to the corn straw powder is (0.5-2):1;

[0029] (2) mixing lignin, 85 wt.% phosphoric acid aqueous solution, urea and 3 wt.% hydrogen peroxide, and reacting at a temperature of 85-90°C to obtain phosphated lignin, wherein the mass ratio of lignin, 85 wt.% phosphoric acid aqueous solution, urea and 3 wt.% hydrogen peroxide is (40-60):(15-25):(0.8-1.5):(1-3);

[0030] (3) Mixing 37 wt.% formaldehyde aqueous solution, 5 wt.% NaOH aqueous solution and melamine, and reacting at a temperature of 60-65° C. to obtain a melamine formaldehyde prepolymer, wherein the mass ratio of the 37 wt.% formaldehyde aqueous solution, the 5 wt.% NaOH aqueous solution and melamine is (12-13): (0.8-1.5): (15-25);

[0031] (4) The phosphated lignin and the melamine formaldehyde prepolymer are mixed, reacted at a temperature of 90-95° C., and then vacuum dried and ground to obtain a flame retardant B, wherein the mass ratio of the phosphated lignin to the melamine formaldehyde prepolymer is (2.5-3.5):1.

[0032] The composite catalyst is a mixture of a delayed catalyst and a gel catalyst, and the delayed catalyst is preferably DXCAT ® C225, gel catalyst preferably DXCAT ® A33, preferably, DXCAT in the composite catalyst ® C225 and DXCAT ® The mass ratio of A33 is 2:1.

[0033] The silane coupling agent is one of KH-550, KH-560, KH-570 and KH-580, all of which are purchased from Hubei Jianghan New Materials Co., Ltd.

[0034] The chain extender is one or two of ethylene glycol and 1,4-butanediol.

[0035] The foaming agent is water.

[0036] The foam stabilizer is a polysiloxane-olefin oxide block copolymer, preferably UA-8883 produced by Hemu New Material Technology Co., Ltd.

[0037] The composite antioxidant is a mixture of AONOX-1035 and AONOX-PEP8T, and preferably the mass ratio of AONOX-1035 to AONOX-PEP8T is 2:1.

[0038] The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material comprises the following steps:

[0039] (1) Preparation of component A: polyether polyol 1, polymer polyol, silane coupling agent, chain extender, flame retardant A, flame retardant B, foaming agent, foam stabilizer and composite catalyst are placed in a reaction kettle, heated to 45°C, stirred at a speed of 35-40 r / min, and stirred for 45-55 min to obtain component A;

[0040] (2) Preparation of component B: react polyether polyol 2, composite antioxidant, pure MDI and liquefied MDI at 80-85°C for 40-50 min to obtain component B, whose -NCO content is 25.7-28.1 wt.%;

[0041] (3) Component A and component B are mixed evenly according to the mass ratio, injected into the mold, and opened and matured for 4-5 minutes to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

[0042] The aging-resistant and highly flame-retardant polyurethane integral skin foam material is applied to automobile steering wheels, PU armrests, headrests, bicycle saddles, motorcycle saddles, and engine hoods.

[0043] Preferably, the flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and the specific preparation process is:

[0044] (1) A 45 wt.% NaOH aqueous solution and a 200-mesh corn straw powder in a mass ratio of 1:1 were placed in a reactor, reacted at 47.5±2.5°C for 1-1.5 hours, and then filtered, dried, washed, neutralized, and freeze-dried to obtain lignin;

[0045] (2) adding lignin, 85 wt.% phosphoric acid aqueous solution, urea and 3 wt.% hydrogen peroxide in a mass ratio of 50:18:1:2 into a reactor, reacting at a temperature of 87.5±2.5°C for 3-4 hours to obtain phosphated lignin;

[0046] (3) Putting melamine and 5 wt.% NaOH aqueous solution in a mass ratio of 20:1 into a reactor, adding 37 wt.% formaldehyde aqueous solution with a mass of 0.6 times that of melamine in three times, mixing, stirring and refluxing at a temperature of 62.5±2.5°C for 2-3 hours to obtain a melamine formaldehyde prepolymer;

[0047] (4) The phosphated lignin and the melamine formaldehyde prepolymer are mixed in a mass ratio of 3:1, stirred and refluxed at a temperature of 92.5±2.5°C for 1.5-2h, and then vacuum dried and ground to obtain a nitrogen-phosphorus synergistically modified lignin flame retardant.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] (1) The aging-resistant and highly flame-retardant polyurethane self-skinning foam material of the present invention has a reasonable design of the catalyst, and adopts a composite catalyst composed of a delayed catalyst and a gel catalyst, which ensures that the material has sufficient fluidity and the product has a good appearance; secondly, the silane coupling agent is used to improve the hydrophobicity of the product, and its moisture and heat resistance and aging performance are improved.

[0050] (2) The aging-resistant and highly flame-retardant polyurethane self-skinning foam material of the present invention uses biomass raw materials to synthesize a high-efficiency flame retardant, broadens the way of biomass resource utilization, and gives the product higher flame retardant properties. By using two flame retardants and a composite antioxidant, the polyurethane self-skinning foam material is given both aging resistance and high flame retardant properties.

[0051] (3) The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material of the present invention has a simple preparation process, and the prepared product has a wide range of applications and can cope with a variety of environmental changes while still having good performance. DETAILED DESCRIPTION

[0052] The present invention is further described below in conjunction with the examples. The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified. The process methods used are conventional methods in the art unless otherwise specified. The parts of the raw materials in the examples and comparative examples are parts by mass.

[0053] The raw materials used in the embodiments and comparative examples are described as follows:

[0054] 10LD8005: Shandong Bluestar Dongda Chemical Co., Ltd.;

[0055] CHP-H45D: Changhua Chemical Technology Co., Ltd.;

[0056] KH-550, KH-560, KH-570, KH-580: Hubei Jianghan New Materials Co., Ltd.;

[0057] DXCAT ® C225, DXCAT ® A33: Shandong Dingxin New Material Technology Co., Ltd.;

[0058] UA-8883: Hemu New Materials Technology (Shanghai) Co., Ltd.;

[0059] INOVOL C305: Shandong Yinuowei New Materials Co., Ltd.;

[0060] AONOX-1035, AONOX-PEP8T: Yitailong (Tianjin) Synthetic Materials Co., Ltd.

[0061] Example 1

[0062] The aging-resistant and highly flame-retardant polyurethane integral skin foam material is made of component A and component B in a mass ratio of 100:50, wherein component A includes the following raw materials in parts by mass:

[0063] 10LD8005: 70 parts;

[0064] CHP-H45D: 30 parts;

[0065] KH-550: 1 part;

[0066] Ethylene glycol: 5 parts;

[0067] 80 mesh expandable graphite: 10 parts;

[0068] Flame retardant B: 10 parts;

[0069] Water: 1.0 part;

[0070] UA-8883: 0.5 parts;

[0071] DXCAT ® C225: 0.4 parts;

[0072] DXCAT ® A33: 0.2 part;

[0073] Composite catalyst: 0.8 parts;

[0074] Component B includes the following raw materials in parts by weight:

[0075] INOVOL C305: 8 parts;

[0076] AONOX-1035: 0.6 parts;

[0077] AONOX-PEP8T: 0.3 parts;

[0078] Pure MDI: 20 parts;

[0079] Liquefied MDI: 75 parts.

[0080] The flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and the specific preparation process is as follows:

[0081] (1) 20 kg of 45 wt.% NaOH aqueous solution and 20 kg of corn straw powder with a particle size of 200 mesh were put into a reactor, reacted at 47.5±2.5°C for 1 hour, and then filtered, dried, washed with water, neutralized, and freeze-dried to obtain lignin;

[0082] (2) 10 kg of lignin, 3.6 kg of 85 wt.% phosphoric acid aqueous solution, 0.2 kg of urea and 0.4 kg of 3 wt.% hydrogen peroxide were added into a reactor and reacted at a temperature of 87.5 ± 2.5 °C for 3 h to obtain phosphated lignin;

[0083] (3) Putting melamine and 5 wt.% NaOH aqueous solution in a mass ratio of 20:1 into a reactor, adding 37 wt.% formaldehyde aqueous solution with a mass of 0.6 times that of melamine in three times, mixing, stirring and refluxing at a temperature of 62.5±2.5°C for 2 hours to obtain a melamine formaldehyde prepolymer;

[0084] (4) Phosphated lignin and melamine formaldehyde prepolymer in a mass ratio of 3:1 were mixed, stirred and refluxed at a temperature of 92.5±2.5°C for 1.5 h, and then vacuum dried and ground to obtain a nitrogen-phosphorus synergistically modified lignin flame retardant.

[0085] The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material comprises the following steps:

[0086] (1) Preparation of component A: 10LD8005, CHP-H45D, KH-550, ethylene glycol, 80 mesh expandable graphite, flame retardant B, water, UA-8883, DXCAT ® C225 and DXCAT ® A33 was put into the reactor and stirred, the temperature was raised to 45°C, the rotation speed was 37.5±2.5r / min, and stirred for 45min to obtain component A;

[0087] (2) Preparation of component B: INOVOL C305, AONOX-1035, AONOX-PEP8T, pure MDI and liquefied MDI were reacted at 82.5±2.5℃ for 40 min to obtain component B, whose -NCO content was 25.7wt.%;

[0088] (3) Component A and component B are mixed evenly in a mass ratio of 100:50, injected into a mold, and molded and cured for 4-5 minutes to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

[0089] Example 2

[0090] The aging-resistant and highly flame-retardant polyurethane integral skin foam material is made of component A and component B in a mass ratio of 100:55, wherein component A includes the following raw materials in parts by mass:

[0091] 10LD8005: 50 parts;

[0092] CHP-H45D: 50 parts;

[0093] KH-560: 3 parts;

[0094] 1,4-Butanediol: 8 parts;

[0095] 100 mesh expandable graphite: 15 parts;

[0096] Flame retardant B: 15 parts;

[0097] Water: 1.0 part;

[0098] UA-8883: 1;

[0099] DXCAT ® C225: 0.8 parts;

[0100] DXCAT ® A33: 0.4 parts;

[0101] Component B includes the following raw materials in parts by weight:

[0102] INOVOL C305: 7 parts;

[0103] AONOX-1035: 0.8 parts;

[0104] AONOX-PEP8T: 0.4 parts;

[0105] Pure MDI: 30 parts;

[0106] Liquefied MDI: 65 parts.

[0107] The flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and the specific preparation process is as follows:

[0108] (1) 20 kg of 45 wt.% NaOH aqueous solution and 20 kg of corn straw powder with a particle size of 200 mesh were put into a reactor, reacted at 47.5±2.5°C for 1.5 h, and then filtered, dried, washed with water, neutralized, and freeze-dried to obtain lignin;

[0109] (2) 10 kg of lignin, 3.6 kg of 85 wt.% phosphoric acid aqueous solution, 0.2 kg of urea and 0.4 kg of 3 wt.% hydrogen peroxide were added into a reactor and reacted at a temperature of 87.5 ± 2.5 °C for 3.5 h to obtain phosphated lignin;

[0110] (3) Melamine and 5 wt.% NaOH aqueous solution in a mass ratio of 20:1 were put into a reaction kettle, and 37 wt.% formaldehyde aqueous solution with a mass of 0.6 times that of melamine was added three times in a batch, and the mixture was stirred and refluxed at a temperature of 62.5±2.5°C for 2.5 hours to obtain a melamine formaldehyde prepolymer;

[0111] (4) Phosphated lignin and melamine formaldehyde prepolymer in a mass ratio of 3:1 were mixed, stirred and refluxed at a temperature of 92.5±2.5°C for 2 hours, and then vacuum dried and ground to obtain a nitrogen-phosphorus synergistically modified lignin flame retardant.

[0112] The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material comprises the following steps:

[0113] (1) Preparation of component A: 10LD8005, CHP-H45D, KH-560, 1,4-butanediol, 100 mesh expandable graphite, flame retardant B, water, UA-8883, DXCAT ® C225 and DXCAT ® A33 was put into the reactor and stirred, the temperature was raised to 45°C, the rotation speed was 37.5±2.5r / min, and stirred for 50min to obtain component A;

[0114] (2) Preparation of component B: INOVOL C305, AONOX-1035, AONOX-PEP8T, pure MDI and liquefied MDI were reacted at 82.5±2.5℃ for 45 min to obtain component B, whose -NCO content was 26.6wt.%;

[0115] (3) Component A and component B are mixed evenly in a mass ratio of 100:55, injected into a mold, and molded and cured for 4-5 minutes to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

[0116] Example 3

[0117] The aging-resistant and highly flame-retardant polyurethane integral skin foam material is made of component A and component B in a mass ratio of 100:45, wherein component A includes the following raw materials in parts by mass:

[0118] 10LD8005: 60 parts;

[0119] CHP-H45D: 40 parts;

[0120] KH-570: 2 parts;

[0121] Ethylene glycol: 5 parts;

[0122] 1,4-Butanediol: 2 parts;

[0123] 80 mesh expandable graphite: 12 parts;

[0124] Flame retardant B: 12 ​​parts;

[0125] Water: 0.8 parts;

[0126] UA-8883: 0.8 parts;

[0127] DXCAT ® C225: 0.6 parts;

[0128] DXCAT ® A33: 0.3 parts;

[0129] Component B includes the following raw materials in parts by weight:

[0130] INOVOL C305: 6 parts;

[0131] AONOX-1035: 0.8 parts;

[0132] AONOX-PEP8T: 0.4 parts;

[0133] Pure MDI: 40 parts;

[0134] Liquefied MDI: 55 parts.

[0135] The flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and the specific preparation process is as follows:

[0136] (1) 20 kg of 45 wt.% NaOH aqueous solution and 20 kg of corn straw powder with a particle size of 200 mesh were put into a reactor, reacted at 47.5±2.5°C for 1.5 h, and then filtered, dried, washed with water, neutralized, and freeze-dried to obtain lignin;

[0137] (2) 10 kg of lignin, 3.6 kg of 85 wt.% phosphoric acid aqueous solution, 0.2 kg of urea and 0.4 kg of 3 wt.% hydrogen peroxide were added into a reactor and reacted at a temperature of 87.5 ± 2.5 °C for 4 h to obtain phosphated lignin;

[0138] (3) Putting melamine and 5 wt.% NaOH aqueous solution in a mass ratio of 20:1 into a reactor, adding 37 wt.% formaldehyde aqueous solution with a mass of 0.6 times that of melamine in three times, mixing, stirring and refluxing at a temperature of 62.5±2.5°C for 3 hours to obtain a melamine formaldehyde prepolymer;

[0139] (4) Phosphated lignin and melamine formaldehyde prepolymer in a mass ratio of 3:1 were mixed, stirred and refluxed at a temperature of 92.5±2.5°C for 2 hours, and then vacuum dried and ground to obtain a nitrogen-phosphorus synergistically modified lignin flame retardant.

[0140] The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material comprises the following steps:

[0141] (1) Preparation of component A: 10LD8005, CHP-H45D, KH-570, 1,4-butanediol, ethylene glycol, 80 mesh expandable graphite, flame retardant B, water, UA-8883, DXCAT ® C225 and DXCAT ® A33 was put into the reactor and stirred, the temperature was raised to 45°C, the rotation speed was 37.5±2.5r / min, and stirred for 55min to obtain component A;

[0142] (2) Preparation of component B: INOVOL C305, AONOX-1035, AONOX-PEP8T, pure MDI and liquefied MDI were reacted at 82.5±2.5℃ for 50 min to obtain component B, whose -NCO content was 27.5wt.%;

[0143] (3) Component A and component B are mixed evenly in a mass ratio of 100:45, injected into a mold, and molded and cured for 4-5 minutes to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

[0144] Example 4

[0145] The aging-resistant and highly flame-retardant polyurethane integral skin foam material is made of component A and component B in a mass ratio of 100:45, wherein component A includes the following raw materials in parts by mass:

[0146] 10LD8005: 55 parts;

[0147] CHP-H45D: 45 parts;

[0148] KH-580: 1.5 parts;

[0149] Ethylene glycol: 4 parts;

[0150] 1,4-Butanediol: 4 parts;

[0151] 80 mesh expandable graphite: 10 parts;

[0152] Flame retardant B: 15 parts;

[0153] Water: 0.9 parts;

[0154] UA-8883: 0.6 parts;

[0155] DXCAT ® C225: 0.6 parts;

[0156] DXCAT ® A33: 0.3 parts;

[0157] Component B includes the following raw materials in parts by weight:

[0158] INOVOL C305: 5 parts;

[0159] AONOX-1035: 1.0 part;

[0160] AONOX-PEP8T: 0.5 parts;

[0161] Pure MDI: 45 parts;

[0162] Liquefied MDI: 50 parts.

[0163] The flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and the specific preparation process is as follows:

[0164] (1) 20 kg of 45 wt.% NaOH aqueous solution and 20 kg of corn straw powder with a particle size of 200 mesh were put into a reactor, reacted at 47.5±2.5°C for 1.5 h, and then filtered, dried, washed with water, neutralized, and freeze-dried to obtain lignin;

[0165] (2) 10 kg of lignin, 3.6 kg of 85 wt.% phosphoric acid aqueous solution, 0.2 kg of urea and 0.4 kg of 3 wt.% hydrogen peroxide were added into a reactor and reacted at a temperature of 87.5 ± 2.5 °C for 4 h to obtain phosphated lignin;

[0166] (3) Putting melamine and 5 wt.% NaOH aqueous solution in a mass ratio of 20:1 into a reactor, adding 37 wt.% formaldehyde aqueous solution with a mass of 0.6 times that of melamine in three times, mixing, stirring and refluxing at a temperature of 62.5±2.5°C for 3 hours to obtain a melamine formaldehyde prepolymer;

[0167] (4) Phosphated lignin and melamine formaldehyde prepolymer in a mass ratio of 3:1 were stirred and refluxed at a temperature of 92.5±2.5°C for 2 hours, and then vacuum dried and ground to obtain a nitrogen-phosphorus synergistically modified lignin flame retardant.

[0168] The method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material comprises the following steps:

[0169] (1) Preparation of component A: 10LD8005, CHP-H45D, KH-580, 1,4-butanediol, ethylene glycol, 80 mesh expandable graphite, flame retardant B, water, UA-8883, DXCAT ® C225 and DXCAT ® A33 was put into the reactor and stirred, the temperature was raised to 45°C, the rotation speed was 37.5±2.5r / min, and stirred for 50min to obtain component A;

[0170] (2) Preparation of component B: INOVOL C305, AONOX-1035, AONOX-PEP8T, pure MDI and liquefied MDI were reacted at 82.5±2.5℃ for 45 min to obtain component B, whose -NCO content was 28.1wt.%;

[0171] (3) Component A and component B are mixed evenly in a mass ratio of 100:45, injected into a mold, and molded and cured for 4-5 minutes to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

[0172] Comparative Example 1

[0173] This comparative example is the same as Example 3, except that KH-570 in component A is removed, and the remaining steps are the same as Example 3.

[0174] Comparative Example 2

[0175] This comparative example is the same as Example 3, except that the flame retardant B in component A is completely replaced by melamine of the same mass fraction, and the other steps are the same as Example 3. Melamine is purchased from Zhejiang Wansheng Co., Ltd.

[0176] Comparative Example 3

[0177] This comparative example is the same as Example 3, except that the composite antioxidant in component B is replaced with AONOX-1035 of the same mass portion, and the remaining steps are the same as Example 3.

[0178] Comparative Example 4

[0179] This comparative example is the same as Example 3, except that component B is replaced as a whole with modified MDI: DG5082 produced by Shandong Yinuowei Polyurethane Co., Ltd., whose -NCO content is 25.5-26.5wt.%, that is, component B is DG5082, and the other steps are the same as Example 3.

[0180] Comparative Example 5

[0181] This comparative example is the same as Example 3, except that the composite catalyst in component A is replaced with DXCAT of the same mass fraction. ® A33, other steps are the same as those in Example 3.

[0182] The aging-resistant and highly flame-retardant polyurethane self-skinning foam materials obtained in Examples 1-4 and Comparative Examples 1-5 were subjected to performance tests, wherein the core density was tested in accordance with GB / T6343-2009; the elongation at break and the tensile strength were tested in accordance with GB / T6344-1996; the oxygen index was tested in accordance with GB / T5454-1997; the flame retardancy was tested in accordance with GB8410-2006; wet heat aging: after 200 hours at a temperature of 95°C and a humidity of 95%, the mechanical properties and dimensional stability of the product were tested; dry aging: after 72 hours at a temperature of 150°C, the mechanical properties and dimensional stability of the product were tested; low temperature: after 24 hours at a temperature of -60°C, the dimensional stability of the product was tested; the water contact angle was tested using the method in ASTMD7490-2013; the dimensional retention rate was tested according to the standard GB / T10801.2-2018, and the test results are shown in Tables 1 and 2.

[0183] Table 1 Mechanical properties, dimensional stability, water contact angle test results

[0184]

[0185] Table 2 Test results

[0186]

[0187] It can be seen from Table 1 and Table 2 that the products prepared in Examples 1-4 of the present invention have excellent resistance to dry and wet heat aging, and have good dry aging loss rate and wet heat aging loss rate as well as high and low temperature dimensional stability; wherein, the dry and wet heat aging loss rates of tensile strength are both lower than 20%, the dry and wet heat aging loss rates of elongation at break are both lower than 25%, and the dry and wet heat aging and low temperature change rates of dimensional stability are low.

[0188] It can be seen from Example 3 and Comparative Example 1 that the addition of a silane coupling agent can significantly improve the hydrophobicity of the polyurethane integral skin foam of the present invention, thereby meeting its use conditions in special weather conditions.

[0189] It can be seen from Example 3 and Comparative Example 2 that the nitrogen-phosphorus synergistically modified lignin flame retardant produced by the present invention can significantly improve the flame retardant properties of the product, so that the flame retardant properties of the prepared polyurethane integral skin foam can reach the level of self-extinguishing when away from fire, non-flammable edges, and the oxygen index is increased to more than 30%.

[0190] The results of Example 3 and Comparative Example 3 show that the composite antioxidant in component B has better high temperature aging resistance than a single antioxidant. At the same time, it can be seen from Comparative Example 4 that the antioxidant component B synthesized by the present invention can not only improve the physical properties of the product, but also improve its aging resistance.

[0191] By comparing Example 3 with Comparative Example 5, it can be seen that the composite catalyst composed of the delayed catalyst and the gel catalyst used in the present invention can ensure sufficient fluidity of the material and ensure a good appearance and excellent performance of the product.

[0192] In summary, the polyurethane integral skin foam material prepared by the present invention has good high temperature aging resistance, moisture and heat aging resistance, flame retardancy and hydrophobicity, so that the product can cope with different environmental changes and has good weather resistance.

Claims

1. An aging-resistant and highly flame-retardant polyurethane integral skin foam material, characterized in that: It is made of component A and component B in a mass ratio of 100: (45-55), wherein component A includes the following raw materials in mass fractions: Polyether polyol 1: 50-70 parts; Polymer polyol: 30-50 parts; Silane coupling agent: 1-3 parts; Chain extender: 5-8 parts; Flame retardant A: 10-15 parts; Flame retardant B: 10-15 parts; Foaming agent: 0.8-1.0 parts; Foam stabilizer: 0.5-1.0 parts; Composite catalyst: 0.6-1.2 parts; Component B includes the following raw materials in parts by weight: Polyether polyol 2: 5-8 parts; Compound antioxidant: 0.9-1.5 parts; Pure MDI: 20-40 parts; Liquefied MDI: 50-75 parts; The polyether polyol 1 has a number average molecular weight of 7000-8000, a functionality of 4-5, and a hydroxyl value of 28.5-32.5 mgKOH / g; The polyether polyol 2 has a number average molecular weight of 400-600, a functionality of 3, and a hydroxyl value of 330-350 mgKOH / g; The flame retardant A is expandable graphite; The flame retardant B is a nitrogen-phosphorus synergistically modified lignin flame retardant, and its specific preparation process is as follows: (1) reacting a 45 wt.% NaOH aqueous solution with corn straw powder at 45-50° C. for 1-1.5 h, then filtering, drying, washing and neutralizing, and freeze-drying to obtain lignin, wherein the mass ratio of the 45 wt.% NaOH aqueous solution to the corn straw powder is (0.5-2):1; (2) mixing lignin, 85 wt.% phosphoric acid aqueous solution, urea and 3 wt.% hydrogen peroxide, and reacting at a temperature of 85-90°C to obtain phosphated lignin, wherein the mass ratio of lignin, 85 wt.% phosphoric acid aqueous solution, urea and 3 wt.% hydrogen peroxide is (40-60):(15-25):(0.8-1.5):(1-3); (3) Mixing 37 wt.% formaldehyde aqueous solution, 5 wt.% NaOH aqueous solution and melamine, and reacting at a temperature of 60-65° C. to obtain a melamine formaldehyde prepolymer, wherein the mass ratio of the 37 wt.% formaldehyde aqueous solution, the 5 wt.% NaOH aqueous solution and melamine is (12-13): (0.8-1.5): (15-25); (4) mixing phosphated lignin and melamine formaldehyde prepolymer, reacting at a temperature of 90-95° C., and then vacuum drying and grinding to obtain flame retardant B, wherein the mass ratio of phosphated lignin to melamine formaldehyde prepolymer is (2.5-3.5):1; The composite catalyst is a mixture of a delayed catalyst and a gel catalyst; The composite antioxidant is a mixture of AONOX-1035 and AONOX-PEP8T.

2. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The expandable graphite has a particle size of 80-100 meshes and can expand by more than 300 times.

3. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The functionality of the polymer polyol is 3, the hydroxyl value is 19.0-23.0 mgKOH / g, and the solid content is 41.0-45.0%.

4. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The silane coupling agent is one of KH-550, KH-560, KH-570 and KH-580.

5. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The chain extender is one or two of ethylene glycol and 1,4-butanediol.

6. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The foaming agent is water.

7. The aging-resistant and highly flame-retardant polyurethane integral skin foam material according to claim 1, characterized in that: The foam stabilizer is a polysiloxane-olefin oxide block copolymer.

8. A method for preparing the aging-resistant and highly flame-retardant polyurethane integral skin foam material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of component A: polyether polyol 1, polymer polyol, silane coupling agent, chain extender, flame retardant A, flame retardant B, foaming agent, foam stabilizer and composite catalyst are placed in a reaction kettle, heated, stirred at a speed of 35-40 r / min, and stirred for 45-55 min to obtain component A; (2) Preparation of component B: react polyether polyol 2, composite antioxidant, pure MDI and liquefied MDI at 80-85°C to obtain component B; (3) Component A and component B are mixed evenly according to a mass ratio, injected into a mold, opened, and aged to obtain an aging-resistant and highly flame-retardant polyurethane self-skinning foam material.

9. An application of the aging-resistant and highly flame-retardant polyurethane integral skin foam material according to any one of claims 1 to 7, characterized in that: It is used in car steering wheels, PU armrests, headrests, bicycle saddles, motorcycle saddles, and engine hoods.

Citation Information

Patent Citations

  • Foam expansion agent compositions containing hydrohaloolefin and water and their uses in the preparation of polyurethane and polyisocyanurate polymer foams

    AU2017204059A1

  • Mine polyurethane self-skinning combination and preparation method thereof

    CN103641979A

Cited By

  • Preparation process and equipment of polyurethane foaming product

    CN122323442A